Psychology of Characters in the Novel Lamising Katresnan by Budiono Setradjaja with the Humanistic Perspective of Abraham Maslow - Zakiyah, Maratuzzakiyah (Abjad Journal of Humanities & Education, 2024)
This research aims to describe the psychological aspects of the characters in the novel Lamising Katresnan by Budiono Santoso Setradjaja using Abraham Maslow's humanistic psychology theory. The primary data source of this research is the novel Lamising Katresnan by Budiono Santosa Setradjaja published by Yayasan Saworo Tino Triatmo (YASATRI) in 2023. Secondary data is in the form of reference articles to support the research. The data is in the form of words, phrases, and sentences contained in the novel. This research focuses on the character's hierarchy of needs, including physiological needs, security needs, love and affection needs for belonging, self-esteem needs, and self-actualization needs needed by the character to run life. The approach used is an objective approach in order to describe the discussion based on the content of the novel. The data collection technique of this research is the structural method to obtain narrative units. Based on the research discussion in the novel Lamising Katresnan, it can be seen: The results of the analysis of the character's needs using Abraham Maslow's humanistic psychology, namely, (1) The physiological needs of the character in the form of the need for rest, food and drink, shelter, and sex, (2) The psychological needs of the character include: (a) the need for a sense of security, namely, (b) the need for a sense of love and affection to belong to the opposite sex, (c) the need for self-esteem from others, (d) the need for self-actualization in the form of career achievement and efforts that have been made.